Development of parallel scales to measure HIV-related stigma. - Visser, Maretha J; Kershaw, Trace; Makin, Jennifer D; Forsyth, Brian W C (AIDS and behavior, 2008)
HIV-related stigma is a multidimensional concept which has pervasive effects on the lives of HIV-infected people as well as serious consequences for the management of HIV/AIDS. In this research three parallel stigma scales were developed to assess personal views of stigma, stigma attributed to others, and internalised stigma experienced by HIV-infected individuals. The stigma scales were administered in two samples: a community sample of 1,077 respondents and 317 HIV-infected pregnant women recruited at clinics from the same community in Tshwane (South Africa). A two-factor structure referring to moral judgment and interpersonal distancing was confirmed across scales and sample groups. The internal consistency of the scales was acceptable and evidence of validity is reported. Parallel scales to assess and compare different perspectives of stigma provide opportunities for research aimed at understanding stigma, assessing the consequences or evaluating possible interventions aimed at reducing stigma.
Keywords: Adolescent; Adult; Factor Analysis, Statistical; Female; HIV Infections; Humans; Male; Middle Aged; Prejudice; Psychometrics; Questionnaires; Reproducibility of Results; Self-Assessment; South Africa; Weights and Measures; Young Adult